Psychological variables related to academic performance in mathematics and statistics in students of first and second years of the psychology faculty of UNMSM - Aliaga Tovar, Jaime (2001)
The goal of this research is to study the relationship between the general intelligence, the academic self concept, the animated features, related to norms and sensitivity, attitude towards mathematics and statistics, the motivation and learning strategies with results in mathematics and statistics of 158 students of the 1st year and 70 ones of the 2nd year of the Psychology Faculty of the Universidad National Mayor de San Marcos. it was proved that in the same way of other studied aspects, the motivating factor Value of the task has a small role, but it is valuable in the results of both courses, and in the same way the learning strategies Met cognition and Self Questionnaire, have this role with the results in math-ematics and Looking for help with the results in statistics.